Complete Chloroplast Genome Sequence of Aquilaria sinensis (Lour.) Gilg and Evolution Analysis within the Malvales Order - Wang, Ying; Zhan, Di-Feng; Jia, Xian; Mei, Wen-Li; Dai, Hao-Fu; Chen, Xiong-Ting; Peng, Shi-Qing (Frontiers in Plant Science, 2016)
Aquilaria sinensis (Lour.) Gilg is an important medicinal woody plant producing agarwood, which is widely used in traditional Chinese medicine. High-throughput sequencing of chloroplast (cp) genomes enhanced the understanding about evolutionary relationships within plant families. In this study, we determined the complete cp genome sequences for A. sinensis. The size of the A.sinensis cp genome was 159,565 bp. This genome included a large single-copy region of 87,482 bp, a small single-copy region of 19,857 bp, and a pair of inverted repeats (IRa and IRb) of 26,113 bp each. The GC content of the genome was 37.11%. The A.sinensis cp genome encoded 113 functional genes, including 82 protein-coding genes, 27 tRNA genes, and 4 rRNA genes. Seven genes were duplicated in the protein-coding genes, whereas 11 genes were duplicated in the RNA genes. A total of 45 polymorphic simple-sequence repeat loci and 60 pairs of large repeats were identified. Most simple-sequence repeats were located in the noncoding sections of the large single-copy/small single-copy region and exhibited high A/T content. Moreover, 33 pairs of large repeat sequences were located in the protein-coding genes, whereas 27 pairs were located in the intergenic regions. Aquilaria sinensis cp genome bias ended with A/T on the basis of codon usage. The distribution of codon usage in A.sinensis cp genome was most similar to that in the Gonystylus bancanus cp genome. Comparative results of 82 protein-coding genes from 29 species of cp genomes demonstrated that A.sinensis was a sister species to G. bancanus within the Malvales order. Aquilaria sinensis cp genome presented the highest sequence similarity of >90% with the G. bancanus cp genome by using CGView Comparison Tool. This finding strongly supports the placement of A.sinensis as a sister to G. bancanus within the Malvales order. The complete A.sinensis cp genome information will be highly beneficial for further studies on this traditional medicinal plant. Moreover, the results will enhance our understanding about the evolution of cp genomes of the Malvales order, particularly with regard to the role of A.sinensis in plant systematics and evolution.